Managerial talent, Investment efficiency and Stock price crash risk - مهدی مرادزاده فرد (مطالعات تجربی حسابداری مالی, 2016)
This study has been implemented with the aim of the development of the researches in the scope of the management effects through investigation of the management ability on the investment decisions and the stock price crash risk. In this regard and in order to measure the managers ability and its related effects on the investment efficiency (in the form of three models) and also its interaction with the element of the reporting quality on the future stock price crash risk (in the form of two models), the Demorgian et al (2013) model has been used. Hence two different statistical samples from the Tehran stock exchange listed companies and with the implementation of the Systematic removal model have been used. Also in order to examine the hypotheses, estimation methods and the assumption of the model, the Panel analysis has been used. our findings show that the managerial talent decreases the underinvestment and reinforces the overinvestment and generally increases the deviation of the expected level of investment. In addition, the results of this study from one hand, show that the managerial talent, meaningfully, decreases the future stock price crash risk and from the other hand it shows that the desirable reporting quality, decreases the future stock price crash risk. But there is no evidence showing the existence of an interactive relationship between capable managers and high reporting quality with future stock price crash risk.